2000
DOI: 10.1046/j.1469-8137.2000.00647.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of photobiont diversity in some Nostoc‐containing lichens

Abstract: Patterns of photobiont diversity were examined in some Nostoc-containing lichens using the nucleotide sequence of the cyanobacterial tRNA Leu (UAA) intron. Lichen specimens collected in northwestern USA were analysed and the sequence data were compared with tRNA Leu (UAA) intron sequences previously obtained from lichens in northern Europe. Generally, it is the species identity of a lichen rather than the geographical origin of the specimen that determines the identity of the cyanobiont. Identical intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
98
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(112 citation statements)
references
References 21 publications
12
98
2
Order By: Relevance
“…Sharing of photobiont genotypes among different host species has also been reported previously among members of the Nephromataceae (Rikkinen et al, 2002;Lohtander et al, 2003;Wirtz et al, 2003), as well as within bryophytes (Costa et al, 2001) and cycads (Costa et al, 1999), but ours is the first study to include large enough sample sizes of both plant symbionts and lichen photobionts to infer that symbiont sharing among unrelated hosts is common. These results contradict earlier studies, based on smaller datasets, which suggested that species-level host specialization was prevalent in cyanolichens and that host species was a better predictor of symbiont genotype than geography (Paulsrud et al, , 2000. Wirtz et al (2003) suggested that the lack of host specialization observed in Antarctic cyanolichens might be due to selection pressure for generalism in harsh environments, but our data indicate that low host specialization can be found also in temperate cyanolichens.…”
Section: Discussioncontrasting
confidence: 99%
“…Sharing of photobiont genotypes among different host species has also been reported previously among members of the Nephromataceae (Rikkinen et al, 2002;Lohtander et al, 2003;Wirtz et al, 2003), as well as within bryophytes (Costa et al, 2001) and cycads (Costa et al, 1999), but ours is the first study to include large enough sample sizes of both plant symbionts and lichen photobionts to infer that symbiont sharing among unrelated hosts is common. These results contradict earlier studies, based on smaller datasets, which suggested that species-level host specialization was prevalent in cyanolichens and that host species was a better predictor of symbiont genotype than geography (Paulsrud et al, , 2000. Wirtz et al (2003) suggested that the lack of host specialization observed in Antarctic cyanolichens might be due to selection pressure for generalism in harsh environments, but our data indicate that low host specialization can be found also in temperate cyanolichens.…”
Section: Discussioncontrasting
confidence: 99%
“…However, intron WH12\1880, from N. commune collected from Surabaya, Java (118 years previously and more than 15 000 km distant), is 100 % identical to ENG\1996 and BBC\1990. The significance of very small differences in sequence similarity is not clear, although Paulsrud et al (2000) were able to use small differences in the variable I regions of tRNA Leu (UAA) introns to compare geographical distribution patterns of Nostoc cyanobionts.…”
Section: Geographical Correlationsmentioning
confidence: 99%
“…It was suggested that the two classes of intron may correlate with different physiological capacities of the cyanobionts, although there were insufficient differences within the conserved regions of the intron to support or reject this proposal. In a recent study, these same authors used tRNA Leu (UAA) intron analysis to study geographical patterns of diversity in Nostoc-containing lichens (Paulsrud et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Lack of diversity within a thallus is consistent with a single event of cyanobiont acquisition during the formation of a bipartite thallus and the formation of new cephalodia by cyanobiont acquisition from older ones. However, the possible occurrence of different Nostoc strains in differrent cephalodia of a single Peltigera venosa thallus (Paulsrud et al, 2000) suggests that, at least in some lichens, the formation of new cephalodia can also involve fresh cyanobiont acquisition from the environment.…”
Section: Specificity and Diversitymentioning
confidence: 99%